The Relationship between Emotional Maturity and Self-Confidence in Class XI Students of SMA Negeri 1 Kasiman - Eka Noviana; Dini Rakhmawati; Venty (Formosa Journal of Applied Sciences, 2023)
The aim of this research is to determine the relationship between emotional maturity and the self-confidence of class XI students at SMA N 1 Kasiman. The method used in this research is quantitative with a correlation research design. Meanwhile, the technique used in this research is saturated sampling which was used for tryouts with a total of 32 students. Based on a simple linear regression test, the result was (r) = 0.649, r calculated > from r table or 0.649 > 0.151, the coefficient of determination value was 42%, and if adjusted to the interpretation table it would show that emotional maturity and self-confidence have a sufficient level of relationship. While the significance value is 10.958, meaning the calculated t value is 10.958 > t table 1.97446, which shows that there is a significant influence between emotional maturity and the self-confidence of class XI students at SMA Negeri 1 Kasiman.